PORTARIA PR/BA N° 222, DE 10 DE JULHO DE 2019 - Fabio Conrado Loula (DMPF-e-Administrativo, n. 132, 16/7/2019, p.21-23., 2019)
Designa os Procuradores para atuarem em substituição: Caroline Rocha Q. Villas Boas, Ruy Nestor Bastos Mello, Juliana de Azevedo Moraes, Flávia Galvão Arruti, Mirella de Carvalho Aguiar, Ovídio Augusto Amoedo machado, Leandro Bastos Nunes, Fábio Conrado Loula, Edson Abdon Peixoto Filho, Domenico D'Andrea Neto, André Luiz Batista Neves, Oliveiros Guanais de Aguiar Filho, Danilo José Matos, Nara Soares Dantas Kruscheswsky, Ana Paula Carneiro Silva Cruz, Edgard de Almeida Castanheira, Bartira Araujo Goes, Vanessa Cristina G. Previtera Vicente. Período: 01/08/2019 a 30/08/2019.